HIGH EXPLOITATION RATE OF ORANGE-DOTTED TUSKFIS CHOERODON ANCHORAGO IN WALLACE LINE, SPERMONDE ISLANDS, MAKASSAR STRAIT, INDONESIA - Tuwo, Ambo (Jurnal Ilmu Kelautan SPERMONDE, 2022)
Orange-dotted tuskfis Choerodon anchorago is Labridae or Wrasse live in coral reefs ecosystem around the world. Wrasse is the second largest marine fish family, was found about 70 genera and about 504 species. Orange-dotted tuskfis is mostly caught by fishermen on the Wallace line on the Spermonde Islands. The Spermonde Islands consists of 60,000 ha of coral reefs. This study aims to assess the exploitation rate of Orange-dotted tuskfis in the Wallace line in the Spermonde Islands, Makassar Strait, Indonesia. Fish samples were collected from the catch in the Spermonde Islands landed at the Fish Landing Port, Makassar City in 2020. Age groups were analyzed by using Bhattacharya method. The growth rate was estimated by using Von Bertalanffy method. Total mortality (Z) was estimated by using the catch curve method. The natural mortality rate (M) was estimated by using Pauly empirical formula. The fishing mortality rate (F) was estimated by using equation . The exploitation rate (E) was estimated by using the Beverton and Holt equations, . The growth rate equation was . The total mortality rate of was 1.38, the natural mortality rate was 0.32, the fishing mortality rate was 1.06, and the exploitation rate was 0.77. Exploitation rates greater than 0.50 indicate that the Orange-dotted tuskfis C. anchorago in on the Wallace line on the Spermonde Islands is overexploited.